The reporting of the sustainability goals and the Sustainable Development Goals (SDGs) in the context of the private sector in South Africa - Mosi, Tumelo (University of the Witwatersrand, Johannesburg, 2022)
Sustainability challenges continue to mount and the fate of this planet lies in a precarious position. In response, the United Nations has introduced a global agreement known as the Sustainable Development Goals (SDGs). These are 17 goals underpinned by 169 targets for addressing social, economic and environmental issues on a global scale. The SDGs seek to do so by unlocking the potential that lies within the private sector and more. The aim of my research was to assess the sustainability goals disclosed by the top 25 Johannesburg Stock Exchange (JSE) listed companies against that of five other countries in 2017. Furthermore, I compared the environmental SDG disclosure of five companies from the metals and mining sector as well as the consumer products sector respectively, within the same period. The sample was selected from the original sample of the top 25 JSE listed companies. Comparisons were done by analysing sustainability/annual/integrated reports of the top 25 JSE listed companies. The results for the sample showed South Africa to be lagging behind the other countries with regards to disclosing sustainability goals in the corporate sustainability reporting for 2017. From 2017 to 2019, the number of reports addressing environmental SDGs from the selected sectors showed an increase. Furthermore, the study companies from the metal and mining sector performed better than those from the consumer products sector with regards to environmental SDG disclosure. However, the environmental SDG score of the study companies from the consumer products sector increased relatively more within the three years of assessment (2017-2019). Variation was also found between the study companies from the two sectors with regards to preference for specific environmental SDGs which included Responsible Consumption and Production (SDG 12), Climate Action (SDG 13), Life Below Water (SDG 14) and Life on Land (SDG 15). Moreover, the iii interviews conducted with the relevant participants revealed that SDG awareness has improved overtime, however internalisation of the SDGs remains the biggest challenge.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2022
Keywords: Sustainability; United Nations; Sustainable Development Goals (SDGs); SDG-8: Decent work and economic growth; SDG-17: Partnerships for the goals